Entrepreneurship and the national system of innovation: What is missing in Turkey? - Elif Bascavusoglu-Moreau (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Although very dynamic and flexible, Turkish SMEs are less innovative than their European counterparts. The analysis undertaken in this paper allows to assess whether this low level of innovative activities is related to a lack of entrepreneurial behaviour and/or to the weaknesses of the Turkish innovation system. Exploring a unique firm level survey realized among 50,000 small- and medium-sized enterprises, we seek to evaluate the impact of firms' behaviour and choices in the presence of entrepreneurial, technological, institutional, and market opportunities, in an emerging country context. Our results highlight the importance of policy measures in building innovative capabilities.
Keywords: O01; O33; L26; 330; entrepreneurship; national systems of innovation; SMEs; innovative capabilities; emerging economies